Hubungan Produksi dan Kandungan Protein Padi Populasi F3 Hasil Persilangan G39 x Milky Rice dan G39 x Ciherang - , Fitriyani; Agus Riyanto; Dyah Susanti; Totok Agung D. H. (Zuriat, 2011)
Rice is one of the commodity that is very important as a staple food for more than 95% of the population in Indonesia. Rice production should be increase continously in line with the increasing population of Indonesia. Therefore, it is important to improve the quality and quantity of the production of rice. Improvement in terms of quality through development of rice with high protein content, beside of its production. Protein content in rice grain be important because it serves as an essential nutrient that can be used in the growth and cell recovery. This research be conducted in the village Sokawera, district Baturaden, Banyumas Regency. The material used is a population of F3 results of crossing with G39 x Milky Rice and G39 x Ciherang. The results showed the highest protein content in population of crossing G39 x Milky Rice is amount 13.42%. and a crossing G39 x Ciherang is amount 13.05%. The value of the correlation of protein content with component output is -0.36. There is no relations between production rice and its protein content.